SURVIVAL OF PATIENTS WITH BLADDER CANCER WHO HAD PARTIAL CYSTECTOMY IS BETTER THAN THOSE WHO HAD RADIOTHERAPY - Prayoga, Denny Achmad; Tranggono, Untung (Indonesian Journal of Urology, 2017)
Objective: To evaluate the survival on patient who had muscle invasive bladder cancer that had been operated or radiotherapy at Sardjito Hospital Yogyakarta. Material & method: From the year 2004-2010, we were data the patients with muscle invasive bladder cancer that had been operated or radiotherapy at Sardjito Hospital. We studied the age when diagnosed, gender, TNM status, histophatologic finding, histophatologic grade, kinds of surgery and status when follow-up. We evaluated the survival of each patient until 5-years post-surgery. We did bivariate analyze to assess the correlation of patient survival and TNM status, histophatologic grade, clinical stadium and kinds of management. We use Kaplan Meier curve to assess the the survival of patient who had muscle invasive bladder cancer. Results: There were 37 patients with bladder cancer, 3 female patients (8.1%) and 34 male patients (91.9%). Five patients were performed radical cystectomy, 4 patients performed partial cystectomy and 28 patients performed TUR-BT and radiotherapy. There were no significant correlation on the patient survival who had muscle invasive bladder cancer with gender, age, stadium, TNM staging, histopathologic grade and kinds of management (p>0.05). From Kaplan Meier curve, we found that the patients survival was better on stadium I, staging T1, N0, M0 and histopathologic G1 grade. While based on kinds of management, patients were performed partial cystectomy had the survival rate better than the one who only performed TUR-BT and radiotherapy. Conclusion: The surgery of partial cystectomy had a better survival rate than TUR-BT and radiotherapy..